ROLE OF PRAGMATISM AS A SCHOOL OF PHILOSOPHY TOWARDS THE EDUCATIONAL SYSTEM - Aadil Hussain Mir; Dr. R. Sivakumar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The term “Pragmatic” denotes a quality characterized by the sensible handling of problems in a manner aligned with prevailing conditions, rather than adhering rigidly to fixed theories, ideologies, or regulations. In the realm of educational philosophy, Pragmatism advocates for an approach wherein education imparts practical skills essential for life and fosters personal development. Renowned educators such as John Dewey and William James espoused Pragmatist principles, which prioritize practical learning that is applicable to real-world contexts. This paper undertakes an examination of Pragmatism and its impact on education, delving into how its fundamental tenets can enhance the effectiveness of teaching and learning processes when applied..